2017
DOI: 10.1021/jacs.7b08176
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene-Bridged Oligo-BODIPYs: Access to Intramolecular J-Aggregates and Superfluorophores

Abstract: A versatile and rapid access to various chain lengths of ethylene-bridged BODIPY motifs was discovered. Corresponding oligomers comprising up to eight monomeric units were studied with respect to their microstructures by photophysical, X-ray crystallographic, and computational means. The investigation of three different dipyrrin cores revealed a crucial dependence on the substitution pattern of the core, whereas the nature of the meso-periphery is less critical. The impact of substituent effects on the conform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 98 publications
3
64
0
2
Order By: Relevance
“…Thus, the less pronounced BET with η BET = 7% (calculated with eqn (5)) is observed in the (C6)-(3)-SiNc system due to the lower dye surface concentration and the higher energy of the BODIPY triplet (∼750 nm). 47,48 Secondly, the ns-decay measured for the range 550-600 nm indicates strong quenching of BODIPY luminescence with η DET = 94%. In contrast to the unreacted dye (3) with lifetime of 7.2 ns (Fig.…”
Section: Ethylene-m-phenyl Bodipymentioning
confidence: 93%
“…Thus, the less pronounced BET with η BET = 7% (calculated with eqn (5)) is observed in the (C6)-(3)-SiNc system due to the lower dye surface concentration and the higher energy of the BODIPY triplet (∼750 nm). 47,48 Secondly, the ns-decay measured for the range 550-600 nm indicates strong quenching of BODIPY luminescence with η DET = 94%. In contrast to the unreacted dye (3) with lifetime of 7.2 ns (Fig.…”
Section: Ethylene-m-phenyl Bodipymentioning
confidence: 93%
“…[63,64] As has been recently shown by Werz's group, chemical fixation of BODIPY units to oligomers can strongly drive J aggregate formation. [65] These authors have also observed that subtle structural modifications can have a pronounced impact on the nature of the aggregates formed.…”
Section: Class (Ii): Bodipys Prone To Aggregationmentioning
confidence: 98%
“…Owing to the ease of tuning their redox, absorption, and emission properties by modifying the ligands, these complexes have found numerous applications as cell imaging agents, active components of optoelectronic devices, and stimuli‐responsive materials . The best‐known class of fluorescent BF 2 complexes is the boron‐dipyrromethenes (BODIPYs, 1 ), which have desirable photophysical properties including intense and narrow absorption and emission bands and, in some cases, near‐unity emission quantum yields ( Φ em ) in dilute solutions …”
Section: Introductionmentioning
confidence: 99%